MACRO-ECONOMETRIC ANALYSIS OF INWARD CAPITAL FLOWS: A CASE OF NIGERIA IN TIMES OF SECURITY CHALLENGES (International Journal of Banking and Finance, 2024)
This study used quarterly data for the period of 2014Q1–2021Q2 to investigate the macro-econometric implications of capital flows to Nigeria in the face of security challenges. The ARDL bounds test technique identified the long-run relationships between macroeconomic dynamics, insecurity, and total capital inflows to Nigeria, while the error correction mechanism (ECM) identified the short-run relationships. The Toda-Yamamoto test was used to determine whether the model variables were causally related or not. The findings pointed to a short-term negative relationship between insecurity, exchange rates, lending rates, and inflows of capital, while a positive relationship was found between industrial production capacity, the consumer price index, and the total inflows of capital to Nigeria, with insecurity, exchange rates, the consumer price index, and lending rates being the most significant variables. In the long run, insecurity, lending rate, and consumer price index had no significant impact on inward capital inflows, while exchange rate and industrial production capacity exerted significant impacts on capital inflows. The lending rate had a negative impact on overall inflows of capital, whereas the exchange rate, industrial production capacity, and consumer price index had positive impacts. The exchange rate and industrial production capacity were the most important variables that affected capital inflows. Based on the ECM, it was realized that aggregate inward capital flows were stabilized by a factor of roughly 47.2% per quarter in order to reach long-run equilibrium. The Toda-Yamamoto causality tests indicated that the interactions between macroeconomic variables and insecurity strongly influenced capital flows to Nigeria. The overall findings suggested that promoting macroeconomic stability and combating insecurity could improve the investment climate, encouraging foreign capital flows into Nigeria.